Acupuncture in the Management of Functional Dyspepsia - Anastasia Yoveline; Murdani Abdullah; Guntur Darmawan; Hasan Mihardja; Saleha Sungkar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
Dyspepsia is an uncomfortable sensation or pain in the upper abdomen which is persisting or recurring. Dyspepsia can be classified into functional and organic dyspepsia. Functional dyspepsia is more commonly found compared to the organic type, approximately 60%. Pharmacologic therapy in the management of functional dyspepsia has not shown optimal results, with the multifactorial etiology of functional dyspepsia as the main challenge. Therefore, the management of functional dyspepsia is widened and involves variety treatment modalities, acupuncture being one of them. Acupuncture is a way of treatment by puncturing needles to particular area on the skin to eliminate pain and treat particular diseases. Acupuncture affects stomach motility and gastric acid secretion in functional dyspepsia patients. Two acupuncture points commonly used in functional dyspepsia are ST 36 and PC 6. Acupuncture can restore gastric motility in patients with functional dyspepsia, who have gastric emptying disturbance. Besides, functional dyspepsia complaints, such as epigastric pain, nausea, vomiting, anorexia, burning sensation, and bloating were found to improve after acupuncture therapy. Side effects of acupuncture are not life threatening with low incidence rate. The effectiveness of acupuncture therapy compared to standard medication shows varies results. Further studies are needed to determine the characteristics of functional dyspepsia patients which could have optimal results through acupuncture therapy. Keywords: epigastric pain, gastric motility, ST 36, PC 6